1989
DOI: 10.1002/ange.19891010306
|View full text |Cite
|
Sign up to set email alerts
|

Zur Struktur der Lithiumverbindungen von Sulfonen, Sulfoximiden, Sulfoxiden, Thioethern und 1,3‐Dithianen, Nitrilen, Nitroverbindungen und Hydrazonen

Abstract: Acceptor-substituierte Lithiumverbindungen LiA-CR'R', bei denen der Acceptor A eine RC(0)-, N=C-, RS02-, RS(0)NR-, RSO-, RS-, 0 2 N -oder RC(N-NR,)-Gruppe sein kann, spielen in der organischen Synthese seit langem eine gro13e Rolle. Ihre Bedeutung ist in den letzten fiinfzehn Jahren nochmals gestiegen, nachdem man in zunehmendem Ma13 gelernt hatte, sie in chemo-, regio-, diastereo-und enantioselektiven Reaktionen einzusetzen. Dabei ist bemerkenswert, dal3 man iiber die Strukturen von solchen Verbindungen, wenn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
3

Year Published

1991
1991
2009
2009

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(27 citation statements)
references
References 213 publications
2
22
0
3
Order By: Relevance
“…[4±6] The monomeric structures of these carbanions have been widely discussed, and C-metalated carbanions, N-metalated ketenimines, and bridged types, shown in Scheme 1, have all been suggested. [7,8] However, these organometallic species generally aggregate in solution, and a small number of reports on lithiophenylacetonitrile have shown dimeric complexes in both tetrahydrofuran (THF) and dimethyl sulfoxide. [8±11] The structure of these a-nitrile-stabilized organolithium species did not become known in detail until Boche et al reported the first X-ray study of solvated lithiophenylacetonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…[4±6] The monomeric structures of these carbanions have been widely discussed, and C-metalated carbanions, N-metalated ketenimines, and bridged types, shown in Scheme 1, have all been suggested. [7,8] However, these organometallic species generally aggregate in solution, and a small number of reports on lithiophenylacetonitrile have shown dimeric complexes in both tetrahydrofuran (THF) and dimethyl sulfoxide. [8±11] The structure of these a-nitrile-stabilized organolithium species did not become known in detail until Boche et al reported the first X-ray study of solvated lithiophenylacetonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the case of C6H5CHCNLi in THF at -108 °C the monomer/dimer ratio is clearly in favour of the monomer [5][6][7], while the same compound seems to be a dimer in dimethyl sulfoxide [8]. Fhe X-ray struc ture determination of lithiated phenyl acetonitrile complexed by tetramethylethylenediamine revealed that this molecule crystallizes as a dimer together with one molecule benzene in the asymmetric unit.…”
mentioning
confidence: 96%
“…The counterion is usually located in the vicinity of the carbon atom. [27] The high kinetic acidity of a-sulfinyl alkanes gives further evidence for a pyramidalized structure of the respective anions. No re-hybridization and thus no overcoming of an intrinsic barrier is necessary.…”
Section: Resultsmentioning
confidence: 97%